2016
DOI: 10.1016/j.immuni.2016.12.001
|View full text |Cite
|
Sign up to set email alerts
|

The Heterogeneity of Ly6Chi Monocytes Controls Their Differentiation into iNOS+ Macrophages or Monocyte-Derived Dendritic Cells

Abstract: SummaryInflammation triggers the differentiation of Ly6Chi monocytes into microbicidal macrophages or monocyte-derived dendritic cells (moDCs). Yet, it is unclear whether environmental inflammatory cues control the polarization of monocytes toward each of these fates or whether specialized monocyte progenitor subsets exist before inflammation. Here, we have shown that naive monocytes are phenotypically heterogeneous and contain an NR4A1- and Flt3L-independent, CCR2-dependent, Flt3+CD11c−MHCII+PU.1hi subset. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
209
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(222 citation statements)
references
References 61 publications
13
209
0
Order By: Relevance
“…In addition to the “neutrophil-like” monocytes, we also detected a smaller, separate subset of Ly6C hi monocytes expressing Cd209a , H2-Ab1 , H2-Aa and Flt3 (Figure S7G), which corresponded to the recently described moDC-producing monocytes (Menezes et al, 2016). Importantly, expression of the cDC transcription factor Zbtb46 was not detected in any of the Ly6C hi monocytes (Figure S7G).…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…In addition to the “neutrophil-like” monocytes, we also detected a smaller, separate subset of Ly6C hi monocytes expressing Cd209a , H2-Ab1 , H2-Aa and Flt3 (Figure S7G), which corresponded to the recently described moDC-producing monocytes (Menezes et al, 2016). Importantly, expression of the cDC transcription factor Zbtb46 was not detected in any of the Ly6C hi monocytes (Figure S7G).…”
Section: Resultssupporting
confidence: 59%
“…A recent report demonstrated that moDCs originate from a subset of Ly6C hi monocytes expressing the genes encoding MHCII, Flt3 and CD209a (Menezes et al, 2016). Consistent with this, we observed much stronger expression of these genes by MDP-derived Ly6C hi monocytes than their GMP-derived counterparts (Figure 5J).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, Ly6C hi monocytic cells have the potential to differentiate into several subsets with antigen-presenting and cross-presenting capacity. 33 This requires upregulation of peptide-presenting MHC class II and class I molecules as well as enhanced expression of co-stimulatory signals, including CD80, CD86, and CD40, which are necessary for proper T cell activation via CD28 and CD40L. 34 Along these lines, it becomes increasingly evident that monocytic cells can give rise to a population of monocytic APCs which are of importance for the stimulation of anti-tumor immune mechanisms during cancer therapy – at least in mouse tumor models.…”
Section: Resultsmentioning
confidence: 99%
“…During tissue injury, monocytes can enter tissues from the peripheral blood and can further differentiate into inflammatory macrophages and reparative/resolving macrophages in situ 55,56,57 . If the cells are chronically exposed to damage-associated molecular pattern molecules (DAMPs) and endosomal TLR ligands, resolution may fail, and macrophages with mixed functions may emerge 58 .…”
Section: Cc-by-nc-nd 40 International License It Is Made Available Umentioning
confidence: 99%